Effect of the CT Table Strap on Radiation Exposure and Image Quality during Cervical Spine CT - Kranz, P.G.; Wylie, J.D.; Hoang, J.K.; Kosinski, A.S. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: The CT table strap may impair shoulder lowering during cervical spine CT. The purpose of this investigation was to evaluate the effect of the CT table strap on radiation exposure and image quality during CT of the cervical spine. MATERIALS AND METHODS: Patients undergoing cervical spine CT were prospectively randomized to having the CT table strap placed around the torso and arms (control group) or around the torso only (intervention group). Radiation exposure, shoulder position, and image quality were evaluated. Potential confounders, including neck diameter and scan length, were also assessed. RESULTS: Fifty-eight patients were enrolled and randomized, and 51 subjects were included in the final study population. There was a 21% decrease in radiation exposure in the intervention group compared with the control group (mean dose-length product, 540 ± 152 versus 686 ± 200 mGy × cm, P = .005). Subjects in the intervention group achieved shoulder lowering of an average of >1 vertebral body lower than the control group (mean shoulder level, 7.7 ± 1.3 versus 6.5 ± 1.3, P = .001). Subjective image quality, determined by the lowest level of spinal cord visibility, was also better in the intervention group (mean cord visibility level, 6.9 ± 1.3 versus 5.9 ± 1.3, P = .006). No differences in neck diameter (P = .28) or scan length (P = .55) were observed between groups. CONCLUSIONS: The CT table strap inhibits shoulder lowering during CT of the cervical spine. Placement of the patient's arms outside the CT table strap results in decreased radiation exposure and increased image quality compared with patients whose arms are placed inside the strap. DLPdose-length productCTDIvolvolume CT dose indexSSDEsize-specific dose estimate